Levantamento de repertório de linguagem em crianças pequenas com síndrome de Down - Aniceto, Gabriela (Universidade Federal de São Carlos, 2017)
Down’s syndrome is defined by its genetic component. There is a set of anatomophysiological commitments that interfere in these children development, especially in language development. To evaluate this instruments and tests were developed, and they may auxiliate in the early detection of possible risks, identifying their potential and making interventional procedures easier. The main goal of this research was to characterize global language development repertoire in children younger than 48 months with Down’s syndrome, with the specific goal of comparing the contributions of Denver’s II Test of Triage Development, Portage’s Operationalized Inventory and Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) for the assessment and characterization of children’s younger than 48 months with Down’s syndrome linguistic repertoire. Participated on this research one boy and three girls with Down’s syndrome between the ages of 14 and 46 months old, whom frequented a public daycare and/or a specialized school in a city in São Paulo’s countryside. The evaluations were made through direct observation and interaction with participants. The evaluation sessions happened in the institutions frequented by the children and had the duration of 1 (one) hour. The number of meetings with each child variated. The sessions were composed of activities required by Denver’s II Test of Triage Development, Portage’s Operationalized Inventory and Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP). With the legal responsible were made presential interviews for the filling of both Brasil’s Criteria Questionnaire and Anamnese Record. Regarding global development, although the children in this study had different ages, they presented similar repertoire and bellow the expected for their age range. The development bellow their age range was also verified regarding the language area. Regarding the instruments used, concludes that they complement each other, and make it possible to verify required abilities in a more specific way. The assessed evaluations matched the literature, pointing that children with Down’s syndrome tend to present a different development from the one seen in children without deficiency in all evaluated areas. The findings obtained with the instruments used allowed to verify the installed development and the potential of the participating children, favoring the elaboration of interventional programs considering the specificities of each children with Down’s syndrome. However, for the deeper comprehension of these children’s development, it is necessary new studies and the use of other instruments.
Keywords: Educação especial; Síndrome de Down; Linguagem; Teste de Triagem de Desenvolvimento de Denver II; Inventário Portage Operacionalizado; Special education; Down’s syndrome; Language; Denver’s II Test of Triage Development; Portage’s Operationalized Inventory; CIENCIAS HUMANAS::EDUCACAO